Metagenomic Insights Into the Diversity of Halophilic Microorganisms Indigenous to the Karak Salt Mine, Pakistan - Cycil, Leena Mavis; DasSarma, Shiladitya; Pecher, Wolf; McDonald, Ryan; AbdulSalam, Maria; Hasan, Fariha (Frontiers in Microbiology, 2020)
Hypersaline regions are terrestrial analogs of the Earth’s primitive ecosystem and extraterrestrial environment. The salt range in Pakistan is considered among a few of the ancient salt deposits in the subcontinent. Karak salt mine is situated at the Northwest end in Pakistan. Despite the fact that halophiles initiated the formation of terrestrial ecosystems, their products and identities remain hidden. Some preliminary studies limited to culture-dependent isolations have been reported. Characterizing the microbiome that spans over centuries of ecosystem development is crucial, given their role in shaping landscape succession and biogeochemical cycles. Here, we used metagenomics techniques to explore the microbial diversity of the Karak salt mine. We used 16S rRNA Illumina amplicon sequencing to characterize the halophilic communities entrapped in Karak mine. The results were interpreted using Illumina Basespace, QIIME, and Cytoscape. Cultures were isolated at 16-25% salinity. Metagenomics data were consistent with our preliminary culturing data, indicating remarkable species to strain-level diversity of unique halophiles. A total of 107099 (brine) and 122679 (salt) reads were obtained. 16S rRNA based sequencing revealed a microbiome with bacteria (66% brine and 72% salt) dominated by Bacteroidetes and Proteobacteria with a strikingly high abundance of Archaea (18% brine and 13% salt). Alpha diversity has higher values in salt than in the brine. The study of the halophiles in the Karak salt mine provides clues for species contributing to the maintenance of biogeochemical cycles of the ecosystem. This is the first report of a metagenomic study of any hypersaline region of Pakistan.